2014
DOI: 10.4269/ajtmh.14-0146
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Rickettsia rickettsii Genotypes Associated with Fatal Rocky Mountain Spotted Fever

Abstract: Abstract. Rocky Mountain spotted fever (RMSF), a tick-borne zoonosis caused by Rickettsia rickettsii, is among the deadliest of all infectious diseases. To identify the distribution of various genotypes of R. rickettsii associated with fatal RMSF, we applied molecular typing methods to samples of DNA extracted from formalin-fixed, paraffin-embedded tissue specimens obtained at autopsy from 103 case-patients from seven countries who died of RMSF. Complete sequences of one or more intergenic regions were amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 40 publications
3
24
0
9
Order By: Relevance
“…While our results of no polymorphisms among Central/ South American isolates was biased because most of these isolates were derived from fatal cases, a recent study reported the same clade distribution as shown in our Fig. 1 when analyzing the intergenic regions of R. rickettsii derived from fatal cases from the United States, Mexico, and Central/South America (21).…”
supporting
confidence: 51%
See 1 more Smart Citation
“…While our results of no polymorphisms among Central/ South American isolates was biased because most of these isolates were derived from fatal cases, a recent study reported the same clade distribution as shown in our Fig. 1 when analyzing the intergenic regions of R. rickettsii derived from fatal cases from the United States, Mexico, and Central/South America (21).…”
supporting
confidence: 51%
“…A more divergent clade was composed of North American isolates that have been ecologically associated with the ticks Dermacentor variabilis and R. sanguineus. As reported in previous studies (10,(19)(20)(21), the North American isolates of R. rickettsii presented relatively high polymorphism compared to that of the Central/South American isolates. Our concatenated analysis showed the formation of 3 North American haplotypes (A, B, and C), each associated with a different tick species (Fig.…”
supporting
confidence: 51%
“…The acquisition and evaluation of clinical samples previously believed suboptimal for a particular molecular method are now more frequently being considered as important sources of diagnostic information. For example, improved nucleic acid extraction technology has facilitated recovery of rickettsial DNA from some types of formalin-fixed, paraffin-embedded skin biopsies or autopsy tissues to allow species-specific PCR and sequence analysis (292,293). Testing of CSF by PCR assays has successfully identified E. chaffeensis (135,159,294).…”
Section: Nucleic Acid Detectionmentioning
confidence: 99%
“…In cases of ehrlichiosis or anaplasmosis in which bone marrow biopsies are performed as part of the investigation of cytopenias, immunostaining of bone marrow biopsy specimens can reveal the diagnosis (156,160). Immunostaining can be particularly useful for diagnosing fatal tickborne rickettsial diseases in tissue specimens from patients who had not developed diagnostic levels of antibodies before death (16,141,293,300). Immunostaining methods are most likely to reveal organisms in patients before or within the first 48 hours after initiating appropriate antibacterial therapy.…”
Section: Immunostaining Of Biopsy or Autopsy Tissuementioning
confidence: 99%
“…Atualmente, o método mais utilizado no diagnóstico é a sorologia, apesar de os anticorpos IgM e IgG aparecerem somente após 7-10 dias do início da doença 19,20 . Existem estudos demonstrando a existência de variações intergênicas entre diferentes isolados de R. rickettsii associadas à virulência 21 , reforçando a importância não somente da identificação mas também da caracterização para o entendimento da doença.…”
Section: ▄ Introduçãounclassified